Austronesian paths and journeys - Fox, James J. (Comparative Austronesian Series., 2021)
This is the eighth volume in the Comparative Austronesian series. Each of the papers in this volume examines various cultural expressions of metaphors of path and journey within a specific Austronesian society. While these extended ethnographic accounts focus on a diversity of metaphoric expressions among widely scattered societies from Taiwan to Timor and from Madagascar to Melanesia and the Pacific, they also point to similar common cultural usages across the Austronesian-speaking world.